The effects of using virtual reality in the rehabilitation of stroke patients: Systematic review - Vidal, Letícia de S.; de Oliveira, Lilian Maria M. C.; Pereira, Tassiane Maria A.; Silva, Janaína de M. (Brazilian Journal of Health and Biomedical Sciences, 2021)
Introdution: Stroke causes several alterations, the more frequent are motor, physical and psychological. Since rehabilitation takes time and can become monotonous, the use of virtual reality can act as a stimulating way to involve the patient in the treatment, seeking to develop its functionality. Objective: The objective of this study was to verify in the available literature the effects of using virtual reality in the treatment of the sequelae of the Stroke, to gain functionality in the upper limbs. Methods: This literature review was based on the PICO strategy, carried out in the databases Lílacs, Pubmed, Scielo and PEDro, using the keywords “physiotherapy AND virtual reality OR exergame OR exergaming AND stroke AND upper limbs”. Complete articles were published in English, Portuguese and Spanish, available and dated between 2015 and 2020, excluding those that were review articles, incomplete and that did not address the topic. Results: As a result, the search found 1,035 articles, of which only 14 met the imposed criteria. Most studies have shown that the use of virtual reality through games has proved to be an efficient resource in the functional rehabilitation of patients with stroke. Presenting itself as a competent complementary to physiotherapeutic treatment in improving fine motor skills, motor behavior of the limbs and cognitive performance, these gains directly influenced the gain in functionality of the samples. Conclusion: The use of virtual reality is useful to assist in the treatment and reduction of sequelae in the upper limbs of patients with stroke, as it promotes greater functional gain, range of motion and improves the dexterity of both the most and the least compromised hand.